Chaetomitrium Nanohystrix - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are densely branched; (2) stem leaves are slightly flattened, with acuminate apices; (3) leaf margins are coarsely spinose-serrate above with often bifid to trifid teeth, and denticulate below; (4) costae are distinct; (5) lamina cells are densely spinose-prorate above, often with bifid to trifid tips at upper ends, and prorate below; (6) setae are 9-10 mm long, densely setulose almost to the base but smooth or sparsely papillose at extreme base; (7) capsules are inclined, with large and lax pustulae all over surface; (8) calyptrae mitriform, hispid all over, and fringed at the base with short hairs.